Prediction method and device for predicting performance of sodium ion battery through asphalt structure
By using the substitution degree of fused ring aromatic hydrocarbon precursors in asphalt hard carbon materials and solid nuclear magnetic NMR technology, the capacity of the low-pressure sodium storage platform of hard carbon is directly predicted, which solves the problem of difficulty in evaluating the sodium storage performance of hard carbon in the low voltage range in the prior art, and improves the design efficiency of carbon materials.
Patent Information
- Application Number
- CN202411685278.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The prior art cannot directly predict the electrochemical sodium storage performance of hard carbon negative electrode through the precursor structure, and the lack of effective and accurate low-voltage sodium storage performance evaluation method makes it difficult to accurately evaluate the complexity of the hard carbon sodium storage mechanism in the low voltage range.
By using the substitution degree of fused-cyclic aromatic hydrocarbon precursors in asphalt hard carbon materials and combining solid nuclear magnetic NMR peaking technology, the relative content of aromatic carbon and aromatic branched carbon is calculated, and the capacity of the low-pressure sodium storage platform of the obtained hard carbon is predicted.
The low-voltage sodium storage platform capacity of hard carbon is realized directly predicted from the precursor structure, which improves the design efficiency of carbon materials, and provides a method to efficiently screen asphalt precursors and prepare high-performance sodium ion battery hard carbon anode.
Smart Images

Figure CN119738729A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for sodium ion batteries, and relates to a method and a device for predicting the degree of substitution of an asphalt-based hard carbon precursor and the capacity of a low-voltage sodium storage platform. Background Art
[0002] Carbon anode materials play a crucial role in determining the performance of full batteries. Among them, pitch-based hard carbon (HC) with curved carbon layers and closed-pore structure is considered to be one of the most promising anode materials. The outstanding low voltage platform capacity (LPP) of HC plays a key role in improving the output voltage and energy density of the full battery. Therefore, the development of advanced HC anodes with excellent LPP performance is crucial to achieve high energy density SIBs.
[0003] The formation mechanism of closed pores in HC and its effect on LPP performance have become a hot topic in the field of SIBs and face major challenges. By adjusting the microcrystalline / amorphous regions of the precursor, stacked carbon layers can be formed in HC to produce closed pores. Among them, pre-oxidation can induce molecular cross-linking through oxygen functional groups, promote the bending of carbon layers, and thus form closed pores. It is widely used in the preparation of HC materials with closed-pore structures. Although many studies have focused on optimizing carbon precursors through pre-oxidation to achieve closed-pore design and thus improve the low-voltage capacitance of HC, existing research lacks a method to directly predict the closed pores and low-voltage sodium storage performance of hard carbon from the structure of the precursor.
[0004] At present, the existing technology cannot directly predict the electrochemical sodium storage performance of the hard carbon negative electrode through the structure of the precursor, and lacks a prediction method from the source between the precursor-hard carbon-electrochemical sodium storage performance. The existing technology lacks an effective and accurate low-voltage sodium storage performance evaluation method, and can only achieve a rough estimate of the electrochemical sodium storage performance based on the structure of the hard carbon material. Due to the complexity of the hard carbon sodium storage mechanism in the low voltage range, it is particularly difficult to accurately evaluate its performance. Most of the existing evaluation methods are aimed at the high voltage range, and the evaluation of the sodium storage performance in the low voltage range is inadequate. If you want to determine whether the precursor can be used to make a sodium battery hard carbon negative electrode, it is impossible without carbonization treatment. Specifically, the sodium storage capacity of hard carbon in the low voltage range mainly comes from the interlayer embedding and extraction behavior of sodium ions in graphite microcrystals in hard carbon materials. However, the existing evaluation methods often find it difficult to accurately capture this process, resulting in large errors in the evaluation results of low-voltage sodium storage performance, which not only affects the comprehensive understanding of the performance of hard carbon materials, but also restricts the further development of sodium ion battery technology. Summary of the invention
[0005] The purpose of the present invention is to provide a prediction method and device for predicting the performance of sodium ion batteries based on asphalt structure. The method can directly utilize the degree of substitution of condensed ring aromatic hydrocarbon precursors in asphalt hard carbon materials to directly predict the low-pressure sodium storage platform capacity of the obtained hard carbon. There is no need to test the performance of the hard carbon obtained by carbonizing the asphalt, thereby effectively improving the design efficiency of carbon materials.
[0006] In order to achieve the above object, the present invention discloses a method for predicting the performance of a sodium ion battery based on asphalt structure, comprising the following steps:
[0007] 1) oxidizing various asphalts and then carbonizing them at high temperature, and then washing with acid and drying them to obtain various asphalt-based hard carbon materials for preparing negative electrodes of sodium ion batteries;
[0008] 2) Using solid nuclear magnetic resonance (NMR) to separate peaks of various asphalt-based hard carbon materials, the substitution degree of various asphalt-based hard carbon materials is calculated by calculating the relative content of aromatic carbon and aromatic branched carbon, and the substitution degree information of each asphalt-based hard carbon material is stored in pairs according to the name and substitution degree data to generate a data set of asphalt-based hard carbon material substitution degree;
[0009] 3) using the various asphalt-based hard carbon materials obtained in step 1) to respectively prepare sodium ion battery negative electrodes, and then using the prepared sodium ion battery negative electrodes to prepare sodium ion batteries;
[0010] 4) Conduct electrochemical tests on all the sodium ion batteries produced to obtain the low voltage platform capacity information of each sodium ion battery, thereby obtaining a data set of closed-cell specific surface area / low voltage platform capacity corresponding to the low voltage platform capacity of the sodium ion battery; among which the closed-cell specific surface area of the asphalt-based hard carbon material is positively correlated with the low voltage platform capacity;
[0011] 5) Using the data set of the degree of substitution of asphalt-based hard carbon materials as the horizontal coordinate and the data set of closed-cell specific surface area / low-voltage platform capacity as the vertical coordinate, linear fitting is performed based on the data set of the degree of substitution of asphalt-based hard carbon materials and the data set of closed-cell specific surface area / low-voltage platform capacity, thereby obtaining fitting line segments of asphalt-based hard carbon materials and closed-cell specific surface area / low-voltage platform capacity. The fitting line segments can be used to predict the low-voltage platform capacity of a sodium-ion battery prepared from any asphalt-based hard carbon material based on the degree of substitution of the asphalt-based hard carbon material.
[0012] Furthermore, all types of asphalt have a condensed ring structure, including low-temperature coal asphalt, medium-temperature coal asphalt, intermediate phase asphalt, high-temperature coal asphalt, petroleum asphalt, and coated asphalt; to improve accuracy, the same type of asphalt can select multiple asphalt products of the same type produced in different production environments for measurement.
[0013] Furthermore, the asphalt high temperature oxidation process is: oxidizing the asphalt once at 300°C for 3 hours, crushing, screening, and then oxidizing it a second time at 300°C for 3 hours.
[0014] Furthermore, the asphalt is subjected to high temperature carbonization treatment, specifically: the asphalt is carbonized in a temperature environment of 1500°C for 2 hours.
[0015] Furthermore, the original spectrum of solid nuclear magnetic resonance (NMR) was separated by using Mestrenova software to obtain a separation curve that simulated the original spectrum with three peaks. The relative content was obtained by calculating the integral areas enclosed by the separation curves of aromatic carbon and aromatic branched chain carbon, respectively. The distribution area of aromatic carbon was 90-148ppm, and the distribution area of aromatic branched chain carbon was 138-148ppm.
[0016] Furthermore, the substitution degree of the asphalt as a precursor was calculated by On the aromatic carbon atom I ar The calculation expression is:
[0017]
[0018] Furthermore, the low voltage platform capacity is the reversible capacity of the low voltage platform of the charging curve.
[0019] Furthermore, the specific surface area of the closed pores of the hard carbon material was measured by BET and small angle X-ray scattering (SAXS), and the calculation expression was S closed pore =S BET -S SAXS .
[0020] Furthermore, in the linear fitting process, it is necessary to ensure that as many data points as coordinates fall on a straight line as possible to reduce the error, wherein the correlation R of the fitted straight line is greater than 0.9.
[0021] A device for predicting the performance of a sodium ion battery from an asphalt structure, characterized in that it includes a processor and a memory, the processor is electrically connected to the memory, the memory is used to store instructions and data, and the processor is used to execute the method for predicting the performance of a sodium ion battery from an asphalt structure as described in any one of claims 1-9; the low-voltage platform capacity of a sodium ion battery made using the asphalt-based hard carbon material is predicted through the degree of substitution data of the asphalt-based hard carbon material, the asphalt-based hard carbon material and the fitting line segment of the closed-pore specific surface area / low-voltage platform capacity, without preparing samples for testing.
[0022] Compared with the prior art, the present invention has the following effective benefits:
[0023] (1) The technology of the present invention is simple and effective. It is a method for predicting the platform capacity of low-voltage sodium storage of hard carbon based on the degree of substitution of precursor Δ of polycyclic aromatic hydrocarbon asphalt precursor. After obtaining the relative content of aromatic carbon and aromatic branched carbon by fitting the solid nuclear magnetic resonance (NMR) peaks, the degree of substitution of polycyclic aromatic hydrocarbon asphalt precursor is calculated, and the platform capacity of low-voltage sodium storage is predicted based on the precursor.
[0024] (2) The present invention has made a breakthrough in the technical field of sodium ion battery negative electrode materials. It mainly solves the problem of lack of prediction of LPP sodium storage performance of asphalt-based hard carbon for sodium ion batteries based on asphalt precursors, and provides a new means for efficiently screening asphalt precursors and preparing high-performance hard carbon negative electrodes for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a TEM image of the asphalt numbered HC-1 in Example 1 of the present invention;
[0026] Figure 2 TEM image of the asphalt numbered HC-2 in Example 2 of the present invention;
[0027] Figure 3 TEM image of the asphalt numbered HC-3 in Example 3 of the present invention;
[0028] Figure 4 is a small angle X-ray diffraction pattern SAXS in an embodiment of the present invention;
[0029] Figure 5 : is the charge and discharge curve of Example 1 of the present invention;
[0030] Figure 6 : is the charge and discharge curve of Example 1 of the present invention;
[0031] Figure 7 : is the charge and discharge curve of Example 1 of the present invention;
[0032] Figure 8 is the fitting curve of the degree of substitution Δ-closed cell specific surface area of the precursors in Examples 1 to 6 of the present invention;
[0033] Fig. 9 This is the Δ-LPP fitting curve of the precursor substitution degree in Examples 1 to 6 of the present invention. DETAILED DESCRIPTION
[0034] The embodiments of the present invention are further described below in conjunction with the accompanying drawings:
[0035] Example 1
[0036] Low-temperature coal tar pitch was selected as the precursor, marked as P1. The pitch was oxidized at 300°C for 3 h and then oxidized at 300°C for another 3 h to obtain oxidized pitch (marked as OP1). The oxidized pitch was carbonized at 1500°C for 2 h in an argon environment in a tubular furnace with a heating rate of 5°C / min. After carbonization, the carbonized pitch sample (marked as HC-1) was washed in a 1% hydrochloric acid (HCl) solution to remove residual impurities. The TEM image is shown in Figure 1. Figure 1 As shown, the yellow line is a structural diagram.
[0037] BET and small angle X-ray scattering (SAXS) were used to examine the closed-cell structure. BET ) is 5.8m 2 g -1 , S SAXS 278m 2 g -1 The closed-cell specific surface area of HC-1 is calculated to be 272.2 m 2 g -1 .
[0038] The steps of preparing sodium ion batteries using the obtained HC-1 are as follows: HC-1, sodium carboxymethyl cellulose and carbon black are weighed in a mass ratio of 8:1:1, and an appropriate amount of distilled water is added. After ball milling at a rate of 200r / min for 6h, the copper foil is evenly coated, and the battery pole piece is obtained after vacuum drying at 60°C for 24h. The obtained battery pole piece is used as the working electrode and the sodium sheet is used as the counter electrode to assemble the sodium ion button battery in the glove box. The electrochemical performance test shows that HC-1 shows a first efficiency of 52%, and the platform capacity of its ramp charge and discharge curve is 17mAh g -1 ,like Figure 5 shown.
[0039] After fitting the solid NMR peaks to obtain the relative contents of aromatic carbon (90-148ppm) and aromatic branched carbon (138-148ppm), the precursor substitution degree of polycyclic aromatic hydrocarbon asphalt was calculated, i.e., aromatic branched carbon On aromatic carbon atoms (I ar ) in the peaks. After peak separation, the aromatic branched carbon of P1 was obtained. and aromatic carbon atoms (I ar ) are 5.9% and 65.5%, and the precursor substitution degree of P1 is calculated to be 9%.
[0040] Example 2
[0041] Medium-temperature coal tar pitch was selected as the precursor, labeled as P2. The asphalt was oxidized at 300°C for 3 h and then oxidized at 300°C for another 3 h to obtain oxidized asphalt (labeled as OP2). The oxidized asphalt was carbonized at 1500°C for 2 h in an argon environment in a tubular furnace with a heating rate of 5°C / min. After carbonization, the carbonized asphalt sample (labeled as HC-2) was washed in a 1% hydrochloric acid (HCl) solution to remove residual impurities. The TEM image is shown in FIG. Figure 2 As shown, the yellow line is a structural diagram.
[0042] BET and small angle X-ray scattering (SAXS) were used to examine the closed-cell structure. BET ) is 4.8m 2 g -1 , S SAXS 1196m 2 g -1 The closed-cell specific surface area of HC-2 is calculated to be 1191.2 m 2 g -1 .
[0043] The steps for preparing sodium-ion batteries using the obtained HC-2 are as follows: weigh HC-2, sodium carboxymethyl cellulose and carbon black in a mass ratio of 8:1:1, add an appropriate amount of distilled water, ball mill at a rate of 200r / min for 6 hours, and evenly coat the copper foil. After vacuum drying at 60°C for 24 hours, the battery electrode is obtained. The obtained battery electrode is used as the working electrode and the sodium sheet is used as the counter electrode to assemble the sodium ion button battery in a glove box. The electrochemical performance test showed that HC-2 showed an initial efficiency of 82%, and the platform capacity was as high as 304mAh g-1; the charge and discharge curves are as shown below Figure 6 shown.
[0044] After fitting the solid NMR peaks to obtain the relative contents of aromatic carbon (90-148ppm) and aromatic branched carbon (138-148ppm), the precursor substitution degree of polycyclic aromatic hydrocarbon asphalt was calculated, i.e., aromatic branched carbon On aromatic carbon atoms (I ar ) in the peaks. After peak separation, the aromatic branched carbon of P2 is obtained. and aromatic carbon atoms (I ar ) are 16.8% and 70%, and the precursor substitution degree of P2 is 24% by calculation.
[0045] Example 3
[0046] The mesophase pitch was selected as the precursor and was labeled as P3. The pitch was oxidized at 300°C for 3 h and then oxidized at 300°C for another 3 h to obtain oxidized pitch (labeled as OP3). The oxidized pitch was carbonized at 1500°C for 2 h in an argon environment in a tubular furnace with a heating rate of 5°C / min. After carbonization, the carbonized pitch sample (labeled as HC-3) was washed in a 1% hydrochloric acid (HCl) solution to remove residual impurities. The TEM image is shown in FIG. Figure 3 As shown, the yellow line is a structural diagram.
[0047] BET and small angle X-ray scattering (SAXS) were used to examine the closed-cell structure. BET ) is 5.0m 2 g -1 , S SAXS 525m 2 g -1 The closed-cell specific surface area of HC-2 is calculated to be 520 m 2 g -1 .
[0048] The steps for preparing sodium-ion batteries using the obtained HC-3 are as follows: weigh HC-3, sodium carboxymethyl cellulose and carbon black in a mass ratio of 8:1:1, add an appropriate amount of distilled water, ball mill at a rate of 200r / min for 6 hours, and evenly coat the copper foil. After vacuum drying at 60°C for 24 hours, the battery electrode is obtained. The obtained battery electrode is used as the working electrode and the sodium sheet is used as the counter electrode to assemble the sodium ion button battery in a glove box. The electrochemical performance test showed that HC-3 showed an initial efficiency of 71%, and the platform capacity was 35mAh g-1; the charge and discharge curves are as shown in Figure 7 shown.
[0049] After fitting the solid NMR peaks to obtain the relative contents of aromatic carbon (90-148ppm) and aromatic branched carbon (138-148ppm), the precursor substitution degree of polycyclic aromatic hydrocarbon asphalt was calculated, i.e., aromatic branched carbon On aromatic carbon atoms (I ar ) in the peaks. After peak separation, the aromatic branched carbon of P3 was obtained. and aromatic carbon atoms (I ar ) are 9.4% and 87.4%, and the precursor substitution degree of P3 is calculated to be 11%.
[0050] Regarding the small angle X-ray diffraction pattern SAXS of the sample in the above-mentioned embodiments 1 to 3, the specific examples are as follows: Figure 4 shown.
[0051] Example 4
[0052] High temperature coal tar pitch was selected as the precursor, marked as P4. The pitch was oxidized at 300°C for 3 h and then oxidized at 300°C for another 3 h to obtain oxidized pitch (marked as OP4). The oxidized pitch was carbonized at 1500°C for 2 h in an argon environment in a tubular furnace with a heating rate of 5°C / min. After carbonization, the carbonized pitch sample (marked as HC-4) was washed in a 1% hydrochloric acid (HCl) solution to remove residual impurities.
[0053] BET and small angle X-ray scattering (SAXS) were used to examine the closed-cell structure. BET ) is 6.7m 2 g -1 , S SAXS 618.7m 2 g -1 The closed-cell specific surface area of HC-4 is calculated to be 612 m 2 g -1 .
[0054] The steps of preparing sodium ion batteries using the obtained HC-4 are as follows: HC-2, sodium carboxymethyl cellulose and carbon black are weighed in a mass ratio of 8:1:1, and an appropriate amount of distilled water is added. After ball milling at a rate of 200r / min for 6h, copper foil is evenly coated, and the battery pole piece is obtained after vacuum drying at 60°C for 24h. The obtained battery pole piece is used as the working electrode and the sodium sheet is used as the counter electrode to assemble the sodium ion button cell in the glove box. The electrochemical performance test shows that HC-4 shows a first efficiency of 73% and a platform capacity of 78mAh g-1.
[0055] After fitting the solid NMR peaks to obtain the relative contents of aromatic carbon (90-148ppm) and aromatic branched carbon (138-148ppm), the precursor substitution degree of polycyclic aromatic hydrocarbon asphalt was calculated, i.e., aromatic branched carbon On aromatic carbon atoms (I ar ) in the peaks. After peak separation, the aromatic branched carbon of P4 was obtained. and aromatic carbon atoms (I ar ) are 10.9% and 72.8%, and the precursor substitution degree of P4 is calculated to be 15%.
[0056] Example 5
[0057] Petroleum pitch was selected as the precursor and was labeled as P5. The pitch was oxidized at 300°C for 3 h and then oxidized at 300°C for another 3 h to obtain oxidized pitch (labeled as OP5). The oxidized pitch was carbonized at 1500°C for 2 h in an argon environment in a tubular furnace with a heating rate of 5°C / min. After carbonization, the carbonized pitch sample (labeled as HC-5) was washed in a 1% hydrochloric acid (HCl) solution to remove residual impurities.
[0058] BET and small angle X-ray scattering (SAXS) were used to examine the closed-cell structure. BET ) is 7m 2 g -1 , S SAXS 796.2m 2 g -1 The closed-cell specific surface area of HC-5 is calculated to be 789.2 m 2 g -1 .
[0059] The steps of preparing sodium ion batteries using the obtained HC-5 are as follows: HC-2, sodium carboxymethyl cellulose and carbon black are weighed in a mass ratio of 8:1:1, and an appropriate amount of distilled water is added. After ball milling at a rate of 200r / min for 6h, copper foil is evenly coated, and the battery pole piece is obtained after vacuum drying at 60°C for 24h. The obtained battery pole piece is used as the working electrode and the sodium sheet is used as the counter electrode to assemble the sodium ion button battery in the glove box. The electrochemical performance test shows that HC-5 shows an initial efficiency of 81% and a platform capacity of 172mAh g-1.
[0060] After fitting the solid NMR peaks to obtain the relative contents of aromatic carbon (90-148ppm) and aromatic branched carbon (138-148ppm), the precursor substitution degree of polycyclic aromatic hydrocarbon asphalt was calculated, i.e., aromatic branched carbon On aromatic carbon atoms (I ar ) in the peaks. After peak separation, the aromatic branched carbon of P5 was obtained. and aromatic carbon atoms (I ar ) are 13.1% and 76.8%, and the precursor substitution degree of P5 is calculated to be 17%.
[0061] Example 6
[0062] The coated asphalt was selected as the precursor and was labeled as P6. The asphalt was oxidized at 300°C for 3 h and then oxidized at 300°C for another 3 h to obtain the oxidized asphalt (labeled as OP6). The oxidized asphalt was carbonized at 1500°C for 2 h in an argon environment in a tubular furnace with a heating rate of 5°C / min. After carbonization, the carbonized asphalt sample (labeled as HC-6) was washed in a 1% hydrochloric acid (HCl) solution to remove residual impurities.
[0063] BET and small angle X-ray scattering (SAXS) were used to examine the closed-cell structure. BET ) is 7.3m 2 g -1 , S SAXS 823m 2 g-1 The closed-cell specific surface area of HC-6 is calculated to be 815.7 m 2 g -1 .
[0064] The steps of preparing sodium ion batteries using the obtained HC-6 are as follows: HC-2, sodium carboxymethyl cellulose and carbon black are weighed in a mass ratio of 8:1:1, and an appropriate amount of distilled water is added. After ball milling at a rate of 200r / min for 6h, copper foil is evenly coated, and the battery pole piece is obtained after vacuum drying at 60°C for 24h. The obtained battery pole piece is used as the working electrode and the sodium sheet is used as the counter electrode to assemble the sodium ion button battery in the glove box. The electrochemical performance test shows that HC-2 shows an initial efficiency of 78%, and the platform capacity is as high as 213mAh g-1.
[0065] After fitting the solid NMR peaks to obtain the relative contents of aromatic carbon (90-148ppm) and aromatic branched carbon (138-148ppm), the precursor substitution degree of polycyclic aromatic hydrocarbon asphalt was calculated, i.e., aromatic branched carbon On aromatic carbon atoms (I ar ) in the peaks. After peak separation, the aromatic branched carbon of P6 was obtained. and aromatic carbon atoms (I ar ) are 13.8% and 68.9%, and the precursor substitution degree of P6 is calculated to be 20%.
[0066] like Figure 8 and Fig. 9 As shown in Table 1, with the degree of substitution of P1-P6 as the horizontal coordinate and the closed-pore specific surface area / low-voltage platform capacity (LPP) of sodium-ion batteries of samples HC-1, HC-2, HC-3, HC-4, HC-5, and HC-6 as the vertical coordinate, the degree of substitution of asphalt-based hard carbon precursor and the closed-pore specific surface area / low-voltage sodium storage platform capacity of hard carbon materials are fitted and calculated, which can predict the low-voltage platform capacity of asphalt-based hard carbons with different degrees of substitution when applied to sodium-ion batteries. The degree of substitution has a strong linear relationship with the low-voltage platform capacity.
[0067] Table 1 Structural parameters of asphalt determined by 13C-CP / MAS-NMR spectroscopy
[0068]
[0069] It can be seen that the prediction method of precursor substitution degree (Δ) and hard carbon low-voltage sodium storage platform capacity based on condensed aromatic hydrocarbon asphalt precursor is intuitive and reliable, which provides a theoretical basis and technical guidance for solving the problem of lack of clear and effective indicators to predict the LPP sodium storage performance of asphalt-based hard carbon.
Claims
1. A method for predicting sodium ion battery performance from asphalt structure, characterized in that: The following steps are involved: 1) oxidizing various asphalts and then carbonizing them at high temperature, and then washing with acid and drying them to obtain various asphalt-based hard carbon materials for preparing negative electrodes of sodium ion batteries; 2) Using solid nuclear magnetic resonance (NMR) to separate peaks of various asphalt-based hard carbon materials, the substitution degree of various asphalt-based hard carbon materials is calculated by calculating the relative content of aromatic carbon and aromatic branched carbon, and the substitution degree information of each asphalt-based hard carbon material is stored in pairs according to the name and substitution degree data to generate a data set of asphalt-based hard carbon material substitution degree; 3) using the various asphalt-based hard carbon materials obtained in step 1) to respectively prepare sodium ion battery negative electrodes, and then using the prepared sodium ion battery negative electrodes to prepare sodium ion batteries; 4) Conducting electrochemical tests on all the produced sodium ion batteries to obtain the low voltage platform capacity information of each sodium ion battery, thereby obtaining a data set of closed-cell specific surface area / low voltage platform capacity corresponding to the low voltage platform capacity of the sodium ion battery; Among them, the closed-pore specific surface area of asphalt-based hard carbon materials is positively correlated with the low-voltage platform capacity; 5) Using the data set of the degree of substitution of asphalt-based hard carbon materials as the horizontal coordinate and the data set of closed-cell specific surface area / low-voltage platform capacity as the vertical coordinate, linear fitting is performed based on the data set of the degree of substitution of asphalt-based hard carbon materials and the data set of closed-cell specific surface area / low-voltage platform capacity, thereby obtaining fitting line segments of asphalt-based hard carbon materials and closed-cell specific surface area / low-voltage platform capacity. The fitting line segments can be used to predict the low-voltage platform capacity of a sodium-ion battery prepared from any asphalt-based hard carbon material based on the degree of substitution of the asphalt-based hard carbon material.
2. The method for predicting sodium ion battery performance from asphalt structure according to claim 1, characterized in that: All kinds of asphalt have a condensed ring structure, including low-temperature coal tar, medium-temperature coal tar, intermediate phase asphalt, high-temperature coal tar, petroleum asphalt, and coated asphalt. To improve accuracy, the same type of asphalt can be measured by selecting multiple asphalt products of the same type produced in different production environments.
3. The method for predicting sodium ion battery performance from asphalt structure according to claim 1, characterized in that: The asphalt high-temperature oxidation process is: the asphalt is subjected to a first high-temperature oxidation, crushing, screening, and a second high-temperature oxidation. The first high-temperature oxidation is 300°C oxidation for 3 hours, and the second high-temperature oxidation is 300°C oxidation for 3 hours.
4. The method for predicting sodium ion battery performance from asphalt structure according to claim 3, characterized in that: The high temperature carbonization treatment of asphalt is specifically as follows: carbonizing the asphalt in a temperature environment of 1500°C for 2 hours.
5. The method for predicting sodium ion battery performance from asphalt structure according to claim 1, characterized in that: The original spectrum of solid nuclear magnetic resonance (NMR) was separated by Mestrenova software to obtain a peak separation curve that simulated the original spectrum with three peaks. The integral areas enclosed by the peak separation curves of aromatic carbon and aromatic branched chain carbon were calculated to obtain the relative content, where the distribution area of aromatic carbon was 90-148ppm, and the distribution area of aromatic branched chain carbon was 138-148ppm.
6. The method for predicting sodium ion battery performance from asphalt structure according to claim 1, characterized in that: The substitution degree of asphalt as a precursor is calculated by calculating the aromatic branched carbon On the aromatic carbon atom I ar The calculation expression is:
7. The method for predicting sodium ion battery performance from asphalt structure according to claim 1, characterized in that: The low voltage platform capacity is the reversible capacity of the low voltage platform of the charging curve.
8. The method for predicting sodium ion battery performance from asphalt structure according to claim 1, characterized in that: The specific surface area of the closed pores of the pitch-based hard carbon material was measured by BET and small-angle X-ray scattering (SAXS), and the calculation expression is S closedpore =S BET -S SAXS .
9. The method for predicting sodium ion battery performance from asphalt structure according to claim 1, characterized in that: During the linear fitting process, it is necessary to ensure that as many data points as possible as coordinates fall on a straight line to reduce errors, and the correlation R of the fitted straight line should be greater than 0.
9.
10. A device using the method for predicting sodium ion battery performance from asphalt structure according to claim 1, characterized in that: It includes a processor and a memory, wherein the processor is electrically connected to the memory, the memory is used to store instructions and data, and the processor is used to execute the prediction method for predicting the performance of a sodium ion battery from an asphalt structure as described in any one of claims 1 to 9; directly utilizing the degree of substitution of condensed aromatic hydrocarbons of the asphalt hard carbon material, the asphalt-based hard carbon material and the fitting line segment of the closed-pore specific surface area / low-voltage platform capacity, the low-pressure sodium storage platform capacity of the sodium ion battery prepared by the obtained asphalt hard carbon material is directly predicted without preparing samples for testing.
Citation Information
Patent Citations
Anode active material for secondary battery and method for producing the same, anode and lithium ion battery using the same
CN107256957A
Preparation method of sulfonated asphalt-based hard carbon for battery negative electrode material
CN110265660A
Hard carbon material, preparation method thereof, and sodium ion battery
CN112397715A
Carbon quantum dot doped hard carbon composite material and preparation method and application thereof
CN113265246A
Asphalt-based hard carbon negative electrode material and preparation method and application thereof
CN116936800A